Design and Construction of a Mobile Web-Based Birth Certificate Registration Application (Case Study: Population and Civil Registry Service of Binjai City) - Dilla Herdianti; Supina Batubara; Melva Sari Panjaitan (Yayasan Sinergi Multidimensi Kreatif, 2024)
The birth certificate registration process often faces obstacles, such as long queues and long processing times at the Population and Civil Registration Office of Binjai City. This study aims to design and develop a mobile web-based application that makes it easier for the public to register for birth certificates online, thereby increasing the efficiency of public services. The system development method used is the Waterfall model, which includes needs analysis, system design, implementation, testing, and maintenance. This application is designed using the HTML5, CSS, JavaScript, and PHP frameworks for a responsive mobile interface, and MySQL as a database. The test results show that this application is able to speed up the registration process and minimize data errors, and receive positive responses from users regarding ease of access and system reliability. With this application, it is hoped that the Population and Civil Registration Office of Binjai City can improve the quality of digital population services